A Student-Run Clinic Serves as a Model for Increasing Patient Access to Osteopathic Manipulative Medicine - Galin, Claire; Shinn, Alyson (Journal of Student-Run Clinics, 2015)
Student-run clinics are a common and valuable educational resource for many medical institutions. While there is literature describing student-run clinics at allopathic medical schools, there is little literature describing student-run clinics at osteopathic institutions. The Touro University Nevada Osteopathic Children’s Clinic (TUNOCC) is a student-run clinic that provides opportunities for Touro University Nevada College of Osteopathic Medicine (TUNCOM) medical students to practice their osteopathic manipulative treatment (OMT). The clinic exclusively serves pediatric and obstetric patients and provides osteopathic care for common musculoskeletal and non-musculoskeletal conditions. This article describes the mission and evidence base for an osteopathic student-run clinic in which students are able to practice osteopathic manipulative medicine and offers insight into the clinic flow, student participation, and leadership.